Magic tricks and psychological science: Analysis of the cognitive process behind magic songs KBG 107 - Zumaroh, Jannati; Muharom Putra, Husain (Direktorat Riset dan Pengabdian kepada Masyarakat UNY, 2025)
This article examines Kidung Sulapan, a 19th-century manuscript from Batavia that describes various traditional magic performances. The study aims to explain how the magic tricks in the manuscript work through the psychological principles of misdirection, optical illusions, gestalt theory, selective attention, and the psychology of emotions, such as awe, surprise, and curiosity. The method used is modern philology to describe the text's content, combined with psychological analysis to interpret the cognitive processes behind the illusions. The results show that magicians exploit audiences' perceptual weaknesses by distracting attention, presenting deceptive visual stimuli, and creating false whole perceptions, for example in the tricks of turning ink into water containing fish or drawing the correct cards. These visual effects trigger strong emotional responses that reinforce the impression of magic. This study confirms that traditional texts not only record performing arts but also contain psychological practices that align with modern theories of perception.